2010
DOI: 10.1038/nri2817
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer as a model for tumour immunotherapy

Abstract: Advances in basic immunology have led to an improved understanding of the interactions between the immune system and tumours, generating renewed interest in approaches that aim to treat cancer immunologically. As clinical and preclinical studies of tumour immunotherapy illustrate several immunological principles, a review of these data is broadly instructive and is particularly timely now that several agents are beginning to show evidence of efficacy. This is especially relevant in the case of prostate cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
278
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(285 citation statements)
references
References 132 publications
0
278
0
3
Order By: Relevance
“…Biologically, using cancer immunotherapy earlier is logical because immunotherapy may be more effective when tumor burden is low (26) and the immune system is more intact (27). As tumors progress, the microenvironment becomes increasingly resistant to an immune response (28).…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, using cancer immunotherapy earlier is logical because immunotherapy may be more effective when tumor burden is low (26) and the immune system is more intact (27). As tumors progress, the microenvironment becomes increasingly resistant to an immune response (28).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested close links among certain infections of the prostate, chronic inflammation, and the development of inflammation-associated prostatic diseases (5)(6)(7)(8)(9)(10). It has been proposed that certain infections of the prostate contribute to the development of chronic inflammation and regenerative "risk factor" lesions, referred to as proliferative inflammatory atrophy, contribute to the development of prostate cancer (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…5). 23 In the coming years, as the results of studies currently underway with the newly approved therapies become available, our understanding of where these treatments fall into place should become clearer.…”
Section: Resultsmentioning
confidence: 99%
“…2). 23 Although this drug has only recently been made available in the United States, it had been an active area of research for quite some time. Two randomized, placebo-controlled, phase III trials were carried out (D9901 24 and D9902A 25 ).…”
Section: Immune Therapymentioning
confidence: 99%